2019
DOI: 10.3390/molecules24091661
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure–Activity Relationships for the Flavonoid-Mediated Inhibition of P-Glycoprotein in KB/MDR1 Cells

Abstract: P-glycoprotein (P-gp) serves as a therapeutic target for the development of inhibitors to overcome multidrug resistance (MDR) in cancer cells. In order to enhance the uptake of chemotherapy drugs, larger amounts of P-gp inhibitors are required. Besides several chemically synthesized P-gp inhibitors, flavonoids as P-gp inhibitors are being investigated, with their advantages including abundance in our daily diet and a low toxicity. The cytotoxicity of daunorubicin (as a substrate of P-gp) to KB/MDR1 cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our results demonstrate that 2,3-saturation and 4-carbonyl of both DHM and taxifolin are involved in key ligand-residue interactions and support DHM as a Pgp ATPase inhibitor. The involvement of 2,3-saturation in binding pocket interactions correlates with SAR studies associating 2,3-saturation with enhanced potency of Pgp inhibition [ 35 ]. As SAR studies are reported for flavonoids similar to DHM, these data, coupled with modeling studies, could be utilized to guide the design of DHM analogs aimed at enhancing Pgp inhibition.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results demonstrate that 2,3-saturation and 4-carbonyl of both DHM and taxifolin are involved in key ligand-residue interactions and support DHM as a Pgp ATPase inhibitor. The involvement of 2,3-saturation in binding pocket interactions correlates with SAR studies associating 2,3-saturation with enhanced potency of Pgp inhibition [ 35 ]. As SAR studies are reported for flavonoids similar to DHM, these data, coupled with modeling studies, could be utilized to guide the design of DHM analogs aimed at enhancing Pgp inhibition.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, recent studies have shown that DHM can enhance the bioavailability of xenobiotic substrates of Pgp, suggesting that DHM acts as a Pgp inhibitor alongside other mechanisms that modify xenobiotic PK profiles [ 32 , 33 , 34 ]. Although the mechanism(s) associated with DHM’s ability to inhibit Pgp are unclear, recent structure-activity relationship (SAR) studies of flavonols and Pgp activity indicate that structural components of DHM are consistent with potent non-competitive Pgp inhibition of ATP hydrolysis [ 35 ]. For example, the 3′-OH, 4′-OH, and 2,3-saturation of DHM are associated with enhanced non-competitive Pgp inhibition [ 33 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual screening can reduce the high cost of drug development and accelerate the discovery of lead compounds and drug candidates. Ligand‐based methods, such as QSAR 152 models, structure‐based approaches such as molecular dynamics and docking 153 and hierarchical cluster analysis 154 could be rational choices as tools for the design of P‐gp inhibitors with high potency. In particular, structure‐based modeling has gained more attention due to the increasing identification of 3D structures of P‐gp.…”
Section: Discussionmentioning
confidence: 99%
“…Such conflicting evidence prevent drugs from proceeding to the later phases of clinical trials and very few receive FDA approval due to reports of poor efficiency and high toxicity levels. The current known computational methods of predicting drug-protein interactions include quantitative structure activity relationship [ 281 ], classification models [ 282 ], and molecular docking [ 283 ], to name a few. Our current knowledge of the PGP structure, will tremendously aid this process as several of these methods rely on the accuracy of the three-dimensional structure of the protein.…”
Section: Current Challenges and Future Possibilities For Drug Develop...mentioning
confidence: 99%